Watering trough, Bai Mancooverbai Ardon Pyaav - Ghosh, Ayan (2023)
The watering trough at the Seth Gangalal V. Mulji Nandlal Pyaav was designed as a drinking spot for horses and other animals used for transport and labour. Made of stone, the watering trough is shaped like a blossoming lotus flower and was filled with water flowing out from the mouths of two lion-faced faucets.